Protein aggregation and neurodegeneration in prototypical neurodegenerative diseases: Examples of amyloidopathies, tauopathies and synucleinopathies - Bourdenx, M.; Koulakiotis, NS; Sanoudou, D.; Bezard, E.; Dehay, B.; Tsarbopoulos, A (Prog NeurobiolProg NeurobiolProg Neurobiol, 2017)
Alzheimer's and Parkinson's diseases are the most prevalent neurodegenerative diseases that generate important health-related direct and indirect socio-economic costs. They are characterized by severe neuronal losses in several disease-specific brain regions associated with deposits of aggregated proteins. In Alzheimer's disease, beta-amyloid peptide-containing plaques and intraneuronal neurofibrillary tangles composed of hyperphosphorylated microtubule-associated protein tau are the two main neuropathological lesions, while Parkinson's disease is defined by the presence of Lewy Bodies that are intraneuronal proteinaceous cytoplasmic inclusions. alpha-Synuclein has been identified as a major protein component of Lewy Bodies and heavily implicated in the pathogenesis of Parkinson's disease. In the past few years, evidence has emerged to explain how these aggregate-prone proteins can undergo spontaneous self-aggregation, propagate from cell to cell, and mediate neurotoxicity. Current research now indicates that oligomeric forms are probably the toxic species. This article discusses recent progress in the understanding of the pathogenesis of these diseases, with a focus on the underlying mechanisms of protein aggregation, and emphasizes the pathophysiological molecular mechanisms leading to cellular toxicity. Finally, we present the putative direct link between beta-amyloid peptide and tau in causing toxicity in Alzheimer's disease as well as alpha-synuclein in Parkinson's disease, along with some of the most promising therapeutic strategies currently in development for those incurable neurodegenerative disorders.
Keywords: alpha-Synuclein/metabolism; Alzheimer Disease/metabolism/*pathology; Animals; Humans; Nerve Degeneration/metabolism/*pathology; Neurodegenerative Diseases/metabolism/pathology; Parkinson Disease/metabolism/*pathology; Protein Aggregation, Pathological/metabolism/*pathology; Tauopathies/metabolism/pathology